IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MELALUI KEGIATAN MEMBATIK “MANGGUR” DI SDN MAYANGAN 2 SEBAGAI SALAH SATU SEKOLAH PENGGERAK DI KOTA PROBOLINGGO - Ika Setyawati; Ludfi Arya Wardana; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study describes the implementation of the P5 Project (Strengthening the Profile of Pancasila Students) through the Mangur batik activity at SDN Mayangan 2, Probolinggo City. The research focuses on the planning, implementation, and evaluation stages of the P5 project. The background of the study is based on the importance of preserving local culture through the P5 project, which aligns with the demands of the Merdeka Curriculum that emphasizes the dimensions of Pancasila. This study aims to strengthen the cultural identity and preservation of local heritage among students amid the advancing era of globalization. The research is a qualitative descriptive study using data collection techniques such as observation, interviews, and documentation. The results show that the implementation of P5 through batik activities successfully instills Pancasila values such as faith and devotion to God Almighty, fosters independence, creativity, mutual cooperation, and love for local culture, as well as enhances students’ understanding of the meaning and philosophy of regional culture.